2000
DOI: 10.1073/pnas.040554697
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of terpenoids: YgbB protein converts 4-diphosphocytidyl-2C-methyl- d -erythritol 2-phosphate to 2C-methyl- d -erythritol 2,4-cyclodiphosphate

Abstract: In many microorganisms, the putative orthologs of the Escherichia coli ygbB gene are tightly linked or fused to putative orthologs of ygbP, which has been shown earlier to be involved in terpenoid biosynthesis. The ygbB gene of E. coli was expressed in a recombinant E. coli strain and was shown to direct the synthesis of a soluble, 17-kDa polypeptide. The recombinant protein was found to convert 4-diphosphocytidyl-2C-methyl-D-erythritol 2-phosphate into 2C-methyl-D-erythritol 2,4-cyclodiphosphate and CMP. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
188
0
4

Year Published

2000
2000
2010
2010

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 238 publications
(196 citation statements)
references
References 23 publications
4
188
0
4
Order By: Relevance
“…Recently, a role in the DXP pathway has been proposed for another member of this superfamily, called YchB in E. coli (indicated by 12 in Fig. 1), which is capable of forming IPP by phosphorylation of an isopentenyl monophosphate (IMP) precursor, and also phosphorylates the essential intermediate phosphocytidyl-2-C-methylerythritol (Lange and Croteau 1999;Luttgen et al 2000). We found that related sequence motifs are present in diphosphomevalonate decarboxylases.…”
Section: Detailing the Motifs: New Sequence Relationships For Three Ementioning
confidence: 82%
“…Recently, a role in the DXP pathway has been proposed for another member of this superfamily, called YchB in E. coli (indicated by 12 in Fig. 1), which is capable of forming IPP by phosphorylation of an isopentenyl monophosphate (IMP) precursor, and also phosphorylates the essential intermediate phosphocytidyl-2-C-methylerythritol (Lange and Croteau 1999;Luttgen et al 2000). We found that related sequence motifs are present in diphosphomevalonate decarboxylases.…”
Section: Detailing the Motifs: New Sequence Relationships For Three Ementioning
confidence: 82%
“…Partial reconstitution of the MEP pathway was performed essentially as described (20)(21)(22). Briefly, partially purified recombinant chlamydial IspD, IspE, and IspF, dialyzed in a 10,000 molecular weight cut-off dialysis cassette (Pierce) against a 20 mM Tris⅐HCl, pH 6.8͞50 mM NaCl solution to remove any contaminating small molecules, were sequentially added to reaction mixtures containing 5 mM CTP, 5 mM ATP, 1 mM DTT, 10 mM MgCl 2 , and 100 mM Tris⅐HCl at pH 6.8, in the presence or absence of 12 M MEP.…”
Section: Methodsmentioning
confidence: 99%
“…In the next step, 2C-methyl-D-erythritol 4-phosphate is converted into the 2C-methyl-D-erythritol 2,4-cyclodiphosphate by the sequential action of three enzymes specified by the ispD, ispE, and ispF genes (19)(20)(21)(22)(23)(24). The last known step of the sequence, the reductive transformation of the cyclic diphosphate into 1-hydroxy-2-methyl-2-(E)-butenyl 4-diphosphate has been identified recently in work with a recombinant Escherichia coli strain engineered for hyperexpression of the ispG gene (previously designated gcpE) (25).…”
mentioning
confidence: 99%